(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth exploration of nouns and their grammatical categories, highlighting their essential role in language structure and communication. It begins by categorizing nouns into types such as proper, common, concrete, abstract, countable, uncountable, and collective, explaining their distinct functions in language. The article then delves into various grammatical categories that shape nouns, including number, gender, case, definiteness, countability, and animacy, emphasizing how these categories influence a noun’s use in a sentence. Furthermore, the article discusses the syntactical roles of nouns as subjects, objects, complements, and modifiers within sentence structures. The conclusion reinforces the importance of understanding nouns in improving linguistic proficiency and appreciating linguistic diversity. This resource is valuable for language learners, linguists, and anyone interested in the intricacies of grammar and sentence formation.